(untitled) (Jahangirnagar University Journal of Biological Sciences, 2016)
Incidence and movement of red pumpkin beetle (RPB), Aulacophora foveicollis on the leaves of sweet gourd, Cucurbita moschata were examined against different management tactics. Result revealed that no significant difference was observed on the number of red pumpkin beetle on young leaf among the plots treated with different management tactics. Mature leaf support more number of RPB compared to that of young leaf and the population of RPB gradually increased from 1st to 3rd week. The mean number of RPB per plant was higher on upper leaf surface as compared to lower leaf surface in all the treated plots during early hours of the day before 10 am. The highest number of RPB was observed at 7:00 am on the upper surface and at 1:00 pm on the lower surface of leaves. The percent reduction of RPB over control on both surfaces of leaf was maximum (100 %) by the use of mosquito net barrier (T3) treated plot at 7:00 and 10:00 am, respectively compared to control. The percent reduction of RPB over control at 1:00 pm ranged 94% to 98% on upper leaf surface and at 4:00 pm ranged 94% to 96% on lower surface in T3 treated plot. The minimum acceptable level of percent reduction (above 87%) of RPB population over control was achieved by application of forwatap 4G @ 4g/plant, Nitro 505 EC @ 1 ml/L, hand picking of adult RPB and planting of musk melon as trap crop. The movement of the adult RPB as expressed through the distribution of the beetles on the upper and lower leaf surfaces of sweet gourd during different hours of a day could be helpful for devising the mechanical and chemical control strategies. Jahangirnagar University J. Biol. Sci. 3(2): 73-80, 2014 (December)